2016
DOI: 10.1042/bcj20160280
|View full text |Cite
|
Sign up to set email alerts
|

Giant mimivirus R707 encodes a glycogenin paralogue polymerizing glucose through α- and β-glycosidic linkages

Abstract: Acanthamoeba polyphaga mimivirus is a giant virus encoding 1262 genes among which many were previously thought to be exclusive to cellular life. For example, mimivirus genes encode enzymes involved in the biosynthesis of nucleotide sugars and putative glycosyltransferases. We identified in mimivirus a glycogenin-1 homologous gene encoded by the open reading frame R707. The R707 protein was found to be active as a polymerizing glucosyltransferase enzyme. Like glycogenin-1, R707 activity was divalent-metal-ion-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Among these eight predicted ORFs, four contained an additional non-overlapping GT domain (two GT2s, one GT6, and one GT60). Functional analyses of GTs in mimiviruses (or in related Paramecium bursaria Chlorella viruses) have demonstrated that some of these enzymes are functional, being able to modify viral collagen-like proteins (74) and polymerize sugars (75). Conservation between PkV RF01 GTs and functionally characterized GTs in viruses and cells is absent or extremely low, which precludes any predictions as to the specific roles of these enzymes in the PkV RF01 life cycle.…”
Section: High Representation Of Glycosyltransferasesmentioning
confidence: 99%
“…Among these eight predicted ORFs, four contained an additional non-overlapping GT domain (two GT2s, one GT6, and one GT60). Functional analyses of GTs in mimiviruses (or in related Paramecium bursaria Chlorella viruses) have demonstrated that some of these enzymes are functional, being able to modify viral collagen-like proteins (74) and polymerize sugars (75). Conservation between PkV RF01 GTs and functionally characterized GTs in viruses and cells is absent or extremely low, which precludes any predictions as to the specific roles of these enzymes in the PkV RF01 life cycle.…”
Section: High Representation Of Glycosyltransferasesmentioning
confidence: 99%
“…Among these eight predicted ORFs, four contained an additional non-overlapping GT domain (two GT2s, one GT6, and one GT60). Functional analyses of GTs in mimiviruses (or in related Paramecium bursaria Chlorella viruses) have demonstrated that some of these enzymes are functional, being able to modify viral collagen-like proteins (Luther et al, 2011) and polymerize sugars (Rommel et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…We found that PkV RF01 encodes key β-oxidation enzymes. sugars (75). Conservation between PkV RF01 GTs and functionally characterized GTs in viruses and cells is absent or extremely low, which precludes any predictions as to the specific roles of these enzymes in the PkV RF01 life cycle.…”
Section: A Nearly Complete Viral-encoded β-Oxidation Pathwaymentioning
confidence: 99%
“…As an adaptation to their site of replication, the viruses encode their own versions of enzymes that are compartmentalized in cells. For example, mimivirus encodes a set of enzymes involved in glycan formation, allowing for the biosynthesis of surface glycoproteins independently of the host secretory pathway. In addition, as noted above (section ), large dsDNA viruses encode sulfhydryl oxidases.…”
Section: Oxidative Folding In Biological Systemsmentioning
confidence: 99%